THE INFLUENCE OF USING HAY DAY GAME TOWARD STUDENTS VOCABULARY MASTERY AT THE SEVENTH GRADE OF SMPN 187 JAKARTA - Syafrizal; Ika Handayani; Raden Fahrizal Juliansyah Sri Prakoso (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2017)
The research objectives were to find out the influence and the result of students’ vocabulary mastery by using Hay Day game at the seventh grade of SMPN 187 Jakarta. The researcher used quantitative method by implementing true experimental design, experimental and control group selected through cluster random sampling. The instrument used in collecting the data was test. The process of teaching vocabulary in this research was effectively done. They followed the learning process enthusiastically both in the class whereas in the home. They also showed good improvement in mastering vocabularies. It can be proven by the result of tests given before and after learning by using Hay Day. The students’ average score in pretest were 63.78 for control and 72.25 for experimental group. The students’ average score in posttest were 76.94 for control and 77.78 for experimental group. Based on the findings, can be concluded that mobile game especially Hay Day can be implemented in teaching vocabulary mastery. The most important thing that should be considered by both of teacher and parents is monitoring students’ activities while using their smartphone.